SAVING MONEY SEBAGAI BENTUK TINDAKAN INVESTASI PEREMPUAN MODERN: STUDI KASUS MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TIDAR - Ines Aulia Lisnur; Wakhidatul Choeriyah; Fella Ardina Cahyani; Ani Fatul Hidayanti; Chusnul Khotimah; Jihad Lukis Panjawa (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
Saving money as a form of investment action is very useful for achieving the desired goals, especially for women. This study aims to analyze the extent of the behavior of female students studying at the Faculty of Economics, Tidar University in carrying out money-saving actions as an investment intention. This research is a qualitative descriptive research. The source of data used is primary data, which is obtained by means of semi-structured interviews with incidental sampling methods and focus group discussion (FGD). The sample data taken was as many as 20 female students from various study programs of the Faculty of Economics, Tidar University. The results of the study show that respondents have good awareness of the importance of financial management and investment. However, there is still a tendency to spend money on non-essential items, influenced by factors such as prestige, trends, lifestyle, FOMO (fear of missing out), and self-love. Therefore, respondents need to improve their knowledge and skills in managing personal and family finances, such as financial literacy, and consider other factors that can affect financial management behavior, such as environmental and social influences.